Physical culture for lifelong healthy participation: Expanding the horizon of individual interest and university engagement in physical education in higher education - Joseph Lobo; Jonar Martin; Jesus Argarin; Joel Tubera; Haynes Angelo Narciso; Genesis Dimalanta (Faculty of Social and Political Science, Universitas Airlangga, 2023)
The degree of an individual’s interest can be conceptualized as their inclination to experience specific emotions toward a particular domain, such as physical education. There is a lack of published scholarly literature exploring the correlation between individual interest and university engagement, particularly within the context of colleges and universities in the Philippines. The primary objective of this study is to enhance the understanding of the correlation between the two variables. Furthermore, the objective of this study is to ascertain the notable disparity in the individual interest and university engagement of students, taking into account their sexes and educational institution. This study uses a quantitative research method. Upon collecting data from a representative sample of college students, it was determined that there was no discernible variation in the levels of individual interest and university engagement based on gender and educational institution. Furthermore, a notable correlation has been identified between individual interest and engagement in higher education. Ultimately, the factors that contribute to university engagement include positive affect and readiness to reengage, stored utility value, stored attainment value, and knowledge-seeking intentions. The present study provides recommendations for future research initiatives and instructors in order to effectively promote lifelong engagement in physical culture among students, encouraging their participation in diverse healthy activities.